Pengaruh Lingkungan, Pribadi, Dan Psikologis Terhadap Keputusan Konsumen Berkunjung Ke Taman Burung Citra Bali International Di Singapadu, Gianyar - Dana, Putu Sumber; Rastini, Ni Made (E-Jurnal Manajemen, 2015)
This study was conducted to determine the influence of environmental, personal, and psychological to the consumer's decision to visit the Bali International Park Bird Imagery in Singapadu, Gianyar. This research was conducted at PT. Image Bali Bird Park International, which is located at Jalan Ngurah Gambir Sergeant Cok, Singapadu, Batubulan, Gianyar. Samples were taken of 120 people with purposive sampling method. Data was collected through questionnaires using a 5-point Likert scale to measure the 12 indicators. The analysis technique used is multiple linear regression. The results of this study indicate that each variable environmental, personal, and psychological positive and significant impact on the consumer's decision to visit the Bali International Park Bird Imagery in Singapadu, Gianyar. This suggests that the environment variables, personal, and psychological can affect consumer's decision to visit the Bali Bird Park International in Singapadu image, Gianyar
Keywords: lingkungan pribadi; psikologis; keputusan konsumen